2020
DOI: 10.35940/ijsce.a3455.0710120
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Risk Management in NG-CDF Construction Projects in Nairobi County

Abstract: Globally, performance of a construction project is primarily judged by cost, time, and quality. Performance of any project is measured by the extent of meeting the standards laid down at the start of the project. Risk management has been conceptualized as having a great bearing on the outcome of projects. The purpose of this study was to investigate risk management in relation to performance of National Government Constituency Development Funded construction projects in Nairobi County. The objectives o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The most accessible, inexpensive and suitable sands are found in rivers, making this the preferred source of extraction in the construction industry, (John, 2021). River sand has been the most preferred choice of fine aggregate due to its availability, affordability and minimal processing needs, (Kiambigi et al, 2018). Combined with gravel, they take the form of "aggregate" in concrete and provide bulk density and strength to construction materials like asphalt and concrete (Koirala and Er., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The most accessible, inexpensive and suitable sands are found in rivers, making this the preferred source of extraction in the construction industry, (John, 2021). River sand has been the most preferred choice of fine aggregate due to its availability, affordability and minimal processing needs, (Kiambigi et al, 2018). Combined with gravel, they take the form of "aggregate" in concrete and provide bulk density and strength to construction materials like asphalt and concrete (Koirala and Er., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the construction industry there have number of studies on BM in general, for instance Mohamed (1996) indicated the need for BM and construction productivity, Garnett and Pickrell (2000) discussed the development and testing of a BM model, Ramirez et al (2004) developed a BM system for evaluating management practices in Chilean, Costa et al (2006) dealt with BM initiative through lessons learnt and improvement of opportunities, El-Mashaleh et al (2007) critiqued the BM models developed to date for the industry, Jang and Park (2009) developed BM based performance management for construction contractors, Kale and Karaman (2012) proposed a model for BM the knowledge management performance of construction firms, Yeung et al (2013) developed a BM model for construction projects in Hong Kong, Ofori-Kuragu et al (2013) in Ghana developed conceptual BM framework for world-class performance, Gwaya et al (2014) developed of a BM model for construction projects in Kenya, K€ arn€ a and Junnonen (2016) discussed the features of a multi-company project evaluation system as a BM tool, Ishak and Azizan (2018) reviewed BM concept in Malaysian construction safety performance, Badihaveli and Vyas (2019) benchmarked construction quality attributes for improving project management delivery and performance, Bonilla and Castillo (2020) developed a BM exercise of minimum management practices in construction. Notwithstanding the countless number of studies on BM, there exist limited knowledge on BM with regard to SME construction firms making measuring and improving their performance difficult.…”
Section: Introductionmentioning
confidence: 99%
“…(2013) developed a BM model for construction projects in Hong Kong, Ofori-Kuragu et al. (2013) in Ghana developed conceptual BM framework for world-class performance, Gwaya et al. (2014) developed of a BM model for construction projects in Kenya, Kärnä and Junnonen (2016) discussed the features of a multi-company project evaluation system as a BM tool, Ishak and Azizan (2018) reviewed BM concept in Malaysian construction safety performance, Badihaveli and Vyas (2019) benchmarked construction quality attributes for improving project management delivery and performance, Bonilla and Castillo (2020) developed a BM exercise of minimum management practices in construction.…”
Section: Introductionmentioning
confidence: 99%